Differences in VO2peak of surfers when paddling in water vs. on a swimbench ergometer - Furr, H. N.; Warner, M. E.; Copeland, T. L.; Robles-Rodriguez, C.; Ponce-González, J. G.; Nessler, J. A.; Newcomer, S. C. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to test the hypothesis that surfers would achieve a higher VO2peak when tested in a swim flume vs. on a swimbench ergometer. Forty-eight surfers (male: 38, female: 10) aged 18-45 years participated in the study. Protocol 1 and 2 both measured heart rate, oxygen consumption (VO2), and respiratory exchange ratio while subjects performed an incremental paddling test both on a swimbench ergometer and in a swim flume. Protocol 2 additionally measured muscle activity and changes in skin temperature. VO2peak was significantly higher in the swim flume (33.03 ± 1.04 ml/kg/min) vs. on the swimbench ergometer (29.86 ± 1.08 ml/kg/min) (p value < 0.001). There were also significant differences in muscle activation and changes in skin temperature between the flume and ergometer (p-value < 0.05). Surfers significantly increased their VO2peak in the water suggesting previous reports of VO2peak likely underestimated surfer's aerobic fitness when measured on a swimbench ergometer. Future research investigating the aerobic fitness of surfers should be conducted while paddling in water or account for the 11% difference in VO2peak when tested on a swimbench ergometer.